2021
DOI: 10.1159/000517116
|View full text |Cite
|
Sign up to set email alerts
|

Changes in PPAR-γ Expression Are Associated with microRNA Profiles during Fetal Programming due to Maternal Overweight and Obesity

Abstract: <b><i>Background:</i></b> There has been a global increase in the prevalence of obesity in pregnant women in recent years. Animal studies have shown that intrauterine environment associated with maternal obesity leads to epigenetic changes. However, the effects of epigenetic changes occurring before birth in response to maternal conditions have not been clearly characterized in humans. <b><i>Objective:</i></b> The aim of the study was to analyze peroxisome prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In one experimental study, reduced PPAR-γ expression in infant cell cultures was found to be associated with maternal obesity. Cells from infant of mothers with obesity showed mRNA (i.e., miR-1301, miR-221, miR-155) and PPAR-γ expression inhibition, and inflammatory cytokine (IL-6, IL-1β, TNF-α) expression upregulation [200]. This suggests that B. thetaiotaomicron may contribute to reducing obesity in infants by protecting AT against inflammatory cytokines by activating PPARγ expression.…”
Section: Bacteroides Sppmentioning
confidence: 94%
“…In one experimental study, reduced PPAR-γ expression in infant cell cultures was found to be associated with maternal obesity. Cells from infant of mothers with obesity showed mRNA (i.e., miR-1301, miR-221, miR-155) and PPAR-γ expression inhibition, and inflammatory cytokine (IL-6, IL-1β, TNF-α) expression upregulation [200]. This suggests that B. thetaiotaomicron may contribute to reducing obesity in infants by protecting AT against inflammatory cytokines by activating PPARγ expression.…”
Section: Bacteroides Sppmentioning
confidence: 94%
“…Gaytán-Pacheco et al. indicated that miR-146a had indirect relation with peroxisome proliferator-activated receptor (PPAR)-γ expression( 41 ), and PPAR-γ participated in adipocyte differentiation and regulation of lipid metabolism ( 42 ). In addition, PPAR-γ was a target mediated by miR-146a ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA profile in mononuclear cells showed a downregulation of miR-155, miR-221, and miR-1301, as well as upregulation of miR-146a in the circulation of newborns from overweight and obese mothers. Moreover, the study showed that in the same samples from newborns, the RNA profile changes induced by overweight mothers and obesity were also associated to alteration in PPAR-γ gene expression, a master regulator of adipogenesis and altered cytokine pro-inflammatory levels in vitro blood mononuclear cell response to metabolic stimuli ( 142 ).…”
Section: Pediatric Obesity Epigeneticsmentioning
confidence: 99%